2020
DOI: 10.1111/andr.12764
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Berberine on reproductive function and spermatogenesis in diabetic rats via inhibition of ROS/JAK2/NFκB pathway

Abstract: Background: Diabetes mellitus (DM) induces impairment of male reproductive system and is considered as a key factor that could partially provide an explanation for male infertility. Thus, understanding the mechanism underlying DM-induced infertility will aid in the identification of novel therapeutic stratagems. Objectives: To delineate the role of ROS/JAK2/NFκB pathway in DM-induced low reproductive function and impaired spermatogenesis. Additionally, to investigate the protective effect of monomeric Berberin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 66 publications
1
11
0
2
Order By: Relevance
“…Excessive generation of ROS is a key trigger of JAK/STAT signaling [4]. Increased ROS levels activate the JAK2/NFκB pathway in the testis, which triggers apoptosis and results in dysfunctional testicles, while JAK2 inhibition reduces oxidative damage and cell apoptosis in the testis [21,22]. In vitro, JAK/STAT phosphorylation was increased in high glucose, and quercetin treated Sertoli cells, implicating JAK's role in diabetes-induced testicular damage [23].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive generation of ROS is a key trigger of JAK/STAT signaling [4]. Increased ROS levels activate the JAK2/NFκB pathway in the testis, which triggers apoptosis and results in dysfunctional testicles, while JAK2 inhibition reduces oxidative damage and cell apoptosis in the testis [21,22]. In vitro, JAK/STAT phosphorylation was increased in high glucose, and quercetin treated Sertoli cells, implicating JAK's role in diabetes-induced testicular damage [23].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with BBR and finasteride significantly restored the GSH, CAT, SOD, (GPx by finasteride, only) and approved the antioxidant properties of the test ingredients. Previous studies have shown that BBR (as an anti-oxidant agent) can prevent damage to testicular tissue, reproductive function, and disruption of spermatogenesis through inhibiting the ROS/JAK2/NFκB pathway and reducing oxidative stress [ 32 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the adaption for a month, 60 six‐week age male wild‐type Sprague–Dawley rats were used to build a type 1 diabetes rat model, and the induction process was based on previous study 3 . After a 12‐week duration of diabetes, intragastric administration was used for a 4‐week treatment of BB (Figure 1).…”
Section: Figurementioning
confidence: 99%